2009
DOI: 10.3989/scimar.2009.73n1183
|View full text |Cite
|
Sign up to set email alerts
|

Variaciones espacio-temporales a pequeña escala en la dinámica poblacional y biología de la gamba blanca <i>Parapenaeus longirostris</i> (Crustacea: Decapoda) en el Mediterráneo occidental

Abstract: SUMMARY: The deep-water rose shrimp Parapenaeus longirostris is a demersal decapod crustacean that is commercially exploited by trawl fleets. The present work compares its population dynamics, biology and condition in two locations (southern and north-western Mallorca in the Balearic Islands, western Mediterranean, separated by a distance of 120 km) with different environmental conditions and explores the relationships between the species and certain environmental factors. Six multidisciplinary bimonthly surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This finding clearly showed that in both species, but particularly in P. sivado, juveniles had a wider thermohaline window, indicating they are able to cope with a wider variability in temperature and salinity conditions. A close dependence on a restricted salinity range has also been shown in deep-sea and continental slope crustaceans, such as Parapenaeus antennatus and Aristeus antennatus (Guijarro et al 2008(Guijarro et al , 2009, while species displacements related to movements of water masses have also been found to occur at wide temporal and geographical scales (Cartes et al 2009(Cartes et al , 2011, linked to relatively small density changes in seawater masses.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This finding clearly showed that in both species, but particularly in P. sivado, juveniles had a wider thermohaline window, indicating they are able to cope with a wider variability in temperature and salinity conditions. A close dependence on a restricted salinity range has also been shown in deep-sea and continental slope crustaceans, such as Parapenaeus antennatus and Aristeus antennatus (Guijarro et al 2008(Guijarro et al , 2009, while species displacements related to movements of water masses have also been found to occur at wide temporal and geographical scales (Cartes et al 2009(Cartes et al , 2011, linked to relatively small density changes in seawater masses.…”
Section: Discussionmentioning
confidence: 74%
“…Mean density and biomass values were calculated by averaging the obtained density values over the total number of hauls made within each combination of geographic sector and depth interval, including zero values. For both species, and for the whole study area, one-way analysis of variance was used to test for significant interannual differences in density (natural logarithmic transformation), after testing for normality of data and homogeneity of variances (Guijarro et al 2008(Guijarro et al , 2009. If no significant interannual differences were detected, a two-way ANOVA was then used considering geographical sectors and 100-m depth strata as factors to test for significant differences.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Mature females are present throughout the year (Levi et al 1995), so the species shows a continuous recruitment pattern (Sobrino et al 2005). A large number of fleets target the species, particularly in the eastern Mediterranean (Politou et al 2008), but it is also exploited in the eastern Atlantic (Benchoucha et al 2008), the Balearic Islands (Guijarro et al 2009) and the Tyrrhenian Sea (Sbrana et al 2006, Milisenda et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…That necessitates being well versed in the conditions under which the catches are made and, in particular, the possible effects of discards when landing based abundance indices are considered. For some species, discards can be assumed to be virtually absent (Guijarro et al, 2009;Sbrana et al, 2006). For others it is not the case (Lorance and Dupouy, 2001); discarding of marketable fish may bias CPUE (Quirijns et al, 2008).…”
Section: Various Origins Of Bias Identified and Choices To Overcome Themmentioning
confidence: 99%
“…We detected clear changes in the trend of landings per fishing trip in 2005 for trawlers and netters. Discussions with professional fishermen and their representatives associated with this work enabled these observations to be linked to the implementation of a selectivity device confirmed later by the Council Regulation (EC) (No 1288(No /2009. To overcome this regulatory bias, we focused the analysis on the 2005-2015 period.…”
Section: Various Origins Of Bias Identified and Choices To Overcome Themmentioning
confidence: 99%